"Everyone else gets ice cream here more often than I do—It burns me up" - Perspectives on Diabetes Care from Nursing Home Residents and their Doctors. Issue 1 (December 2016) - Barnhart, Caroline; McClymont, Keelan; Smith, Alex; Au-Yeung, Alvin; Lee, Sei
Abstract Background To explore the perspectives of nursing home (NH) residents with diabetes and their doctors regarding the burdens of living with diabetes and diabetes treatments. Methods Qualitative study of nursing home residents aged 65 and older with diabetes (n  = 14) and nursing home physicians (n  = 9) at a Department of Veterans Affairs nursing home (known as the Community Living Center). A semi-structured interview was used to elicit nursing home residents' and physicians' perspectives on the burden of diabetes and diabetes treatments. Transcripts were analyzed using constant comparative methods. Results The mean age of the nursing home residents was 74; Most (93 %) were male and 50 % self-identified themselves as white. The mean age of nursing home physicians was 39 and 55 % were geriatricians. Dietary restrictions, loss of independence and fingersticks/insulin were noted to be the most burdensome aspects of diabetes. Nursing home residents with a more positive outlook were generally more engaged in their care, while nursing home residents with a more pessimistic outlook were less engaged, allowing their physicians to assume complete control of their care. While physicians noted the potential negative impact of dietary restrictions, nursing home residents' comments suggest that physicians underestimate the burden of dietary restrictions. Conclusions Veterans Affairs nursing home residents were substantially burdened by their diabetes treatments, especially dietary restrictions and fingerstick monitoring. Since there is little evidence that dietary restrictions improve outcomes, fewer dietary restrictions may be appropriate and lead to lower treatment burdens for nursing home residents with diabetes.